Engineering application of reverse engineering technology - Tóth, Dániel (Design of Machines and Structures, 2024)
Scanners operating on the optical principle are devices for recording the phys-ical geometry of bodies suitable for non-contact measurement which work in the visible light range. These use the difference in contrasts and the strength of the reflected light for the measurement, by using the classic triangulation principle. This article focuses on re-verse engineering technologies and optical scanning process.